A rare coexistence of methicillin-resistant Staphylococcus aureus pneumonia with chronic necrotizing pulmonary aspergillosis in a not-so-sick patient:A case report (Indian Journal of Case Reports, 2025)
We present a case of a 68-year-old female, a known case of diabetes who presented with a short history of fever and cough. Failure to respond to oral antibiotics led to further investigations which revealed the coexistence of methicillin-resistant Staphylococcus aureus pneumonia and chronic necrotising pulmonary aspergillosis. Dual infection with unusual pathogens in a not-so-sick patient with a short history of illness makes the case worth reporting. It highlights that, in people living with diabetes, rare and unusual presentations are common; hence keeping a high degree of suspicion, detailed workup including tissue diagnosis aids in early diagnosis and good clinical outcomes.